The Role of Dividend and Debt Policy in Increasing Firm Value in the Food and Beverage Subsector: An Empirical Analysis on the Indonesia Stock Exchange - Niken Probondani Astuti; Nurkhalifa Nurkhalifa; Rizal Bakri (PT. Anagata Sembagi Education, 2024)
This study was conducted to determine how debt decisions and dividend policies impact the value of companies in the food & beverage industry listed on the Indonesia Stock Exchange. The sample selection used a purposive sampling method with the criteria of 35 companies in the food & beverage sub-sector that distributed cash dividends from 2018 - 2022. To perform this analysis, Eviews 12 was used. This includes estimating panel data regression equation models, classical assumption testing, statistical analysis, and hypothesis testing. This study finds that debt policy has a negative and significant impact on company value, while dividend policy has a positive and significant impact